Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000-2029; 2010-2019; afrique; approches et analyses; care; corps; discipline; fem1000; feminisme noir; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppression; thématiques; violences; émotions; études culturelles

Gender (in)securities: Surveillance and transgender bodies in post 9/11 era of neoliberalism - Quinan, Christine (Security/mobility: politics of movement, 2017)
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; citoyenneté; corps; genre; hétérosexisme; identités; législation; personnes trans; périodes historiques; queer; racisme; ressource en ligne; solidarité; systèmes d'oppression; thématiques; violences

Men's intrusion, women's embodiment: a critical analysis of street harassment - Vera-Gray, Fiona (Routledge, 2017)
Research on violence against women tends to focus on topics such as sexual assault and intimate partner violence, arguably to the detriment of investigating men’s violence and intrusion in women’s everyday lives. The reality and possibility of the routine intrusions women experience from men in public space – from unwanted comments, to flashing, following and frottage – are frequently unaddressed in research, as well as in theoretical and policy-based responses to violence against women. Often at their height during women’s adolescence, such practices are commonly dismissed as trivial, relatively harmless expressions of free speech too subjective to be legislated against. Based on original empirical research, this book is the first of its kind to conduct a feminist phenomenological analysis of the experience for women of men’s stranger intrusions in public spaces. It suggests that intrusion from unknown men is a fundamental factor in how women understand and enact their embodied selfhood. This book is essential reading for academics and students involved in the study of violence against women, feminist philosophy, applied sociology, feminist criminology and gender studies.
Keywords: 2000 à aujourd'hui; 2010-2019; agentivité; angleterre; approches et analyses; corps; discipline; europe; harcèlement de rue; patriarcat; phénoménologie; périodes historiques; régions géographiques; sciences humaines; sociologie; sofia; systèmes d'oppression; thématiques; violences

Le ventre des femmes : capitalisme, racialisation, féminisme - Vergès, Françoise (Albin Michel, 2017)
Dans les années 1960-1970, l'État français encourage l'avortement et la contraception dans les départements d'outre-mer alors même qu'il les interdit et les criminalise en France métropolitaine. Comment expliquer de telles disparités? Partant du cas emblématique de La Réunion où, en juin 1970, des milliers d'avortements et de stérilisations sans consentement pratiqués par des médecins blancs sont rendus publics, Françoise Vergés retrace la politique de gestion du ventre des femmes, stigmatisées en raison de la couleur de leur peau. Dès 1945, invoquant la «surpopulation» de ses anciennes colonies, l'État français prône la régulation des naissances et l'organisation de l'émigration; une politique qui le conduit à reconfigurer à plusieurs reprises l'espace de la République, provoquant un repli progressif sur l'Hexagone au détriment des outre-mer, où les abus se multiplient. Françoise Vergés s'interroge sur les causes et les conséquences de ces reconfigurations et sur la marginalisation de la question raciale et coloniale par les mouvements féministes actifs en métropole, en particulier le MLF. En s'appuyant sur les notions de genre, de race, de classe dans une ère postcoloniale, l'autrice entend faire la lumière sur l'histoire mutilée de ces femmes, héritée d'un système esclavagiste, colonialiste et capitaliste encore largement ignoré aujourd'hui.
Keywords: 1900-1999; 1960-1969; 1970-1979; afrique; approches et analyses; corps; discours dominant; europe; fem3100; feminisme décolonial; france; maternité; premier cycle; périodes historiques; racisme; régions géographiques; sexisme; système colonial; systèmes d'oppression; thématiques; violences; île de la réunion